The Spatial Void: Indonesia's Political Ecology of Legal Contradictions Created the humanities incident of flash floods in Sumatra’s 2025 - Muhammad Ridhwan; Hasanul Bulqiyah; Fangela Myas Sari; Lukiyana Lukiyana (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This article examines the regulatory tensions between Law No. 23/2014 on Regional Government, which emphasizes the reconcentration of authority, and Law No. 6/2023 (the Job Creation Law), which mandates the centralization of licensing through a deregulatory framework. The study focuses on Sumatra, a region characterized by high ecological vulnerability and its role as a strategic hub for extractive expansion. Utilizing a juridical-normative methodology complemented by secondary spatial analysis, this study finds that ambiguities in environmental oversight authority have catalyzed a surge in deforestation and recurrent hydrometeorological disasters. The results demonstrate that deregulation, pursued under the guise of streamlining investment, has systematically dismantled the ecological protection functions previously vested in regional authorities. This "institutional displacement" has created a governance vacuum that prioritizes short-term economic output over the bio-geophysical stability of the Sumatran landscape. The findings suggest that without a substantive synchronization of regulations that restores "ecological veto" power to local governments, the island remains at critical risk of systemic ecosystem collapse.